Dampak Perubahan Iklim pada Sosial Ekonomi Nelayan dan Pembudidaya Ikan (Universitas Teknologi Muhammadiyah Jakarta (UTM Jakarta), 2025)
Climate change represents a global challenge that significantly impacts the fisheries sector, particularly impacting fishermen and fish farmers. This article analyzes the effects of climate change on the socio-economic aspects of fisheries stakeholders and examines potential adaptation strategies that can be implemented. Utilizing a descriptive qualitative method, this study identifies key obstacles and explores developable solutions aimed at enhancing the resilience of the fisheries sector amidst climate change.